Nepal: a history from the earliest times to the present - Michaels, Axel (Oxford University Press, 2024)
Until 1951 Nepal was closed to the world, landlocked between the strongest Asian powers, India and China. With its exceptional landscape, it touts the highest mountains and the greatest biodiversity on earth. It is best known as the home of Mt. Everest and holds particular fascination for those interested in climbing the Himalayas. Having long maintained its self-imposed isolation, the nation is one of the least developed in the world. Yet it is inhabited by a remarkably diverse population of 125 ethnic groups, 123 languages, and numerous religions, most notably Hinduism and Buddhism.In this book, South Asia expert Axel Michaels covers the history of Nepal from prehistoric times and the period of the Licchavi dynasty through more recent developments, such as the rise of the republic, the first elections challenged by the Maoist insurgency (1996-2006), and the royal massacre in 2001. Chapters discuss the different principalities on the territory, among them the mysterious and legendary Mustang and Sherpa realms. Since the eighteenth century, these domains have been bundled into a contentious national history. Thus, going well beyond the center of power in the Kathmandu Valley, the book examines Nepal's relations with neighboring cultures in India, Tibet, and China, as well as the influence of British colonial power. It particularly focuses on its rich history of arts, architecture, and handicrafts. Although the Buddha was born in Nepal, the country is the world's last Hindu kingdom and is also a stronghold of Tantric traditions, shamanism, and many folk religions whose festivals and rituals mark daily life. Based on a wealth of primary sources in Nepali, Sanskrit, and other indigeneous languages, Nepal offers a comprehensive and updated history of this unique culture and history